Competing faiths under colonial rule: Islamic expansion, Christian missionaries, and the emergence of mualaf in the making of religious identity in Sabah - Zaifuddin Md Rasip; Suhailah Abdul Muin; Habibah@Artini Ramlie; Dg. Hafizah Ag. Basir; Rozeeda Kadri (Human Resource Management Academic Research Society, 2025)
This article examines the historical development of Islamic expansion and the emergence of Muslim converts (mualaf) in Sabah during the British colonial period. It highlights the interplay between Islamic proselytization, Christian missionary efforts, colonial governance, and indigenous belief systems. Islam was first introduced in the 14th century through maritime trade with Brunei, Sulawesi, and Mindanao, followed by gradual conversions supported by Bruneian political influence and intermarriage. However, the 19th-century British administration actively supported Christian missions through legal, institutional, and infrastructural means—including access to education and healthcare—while Islamic propagation faced restrictions and lacked state backing. Using a qualitative approach based on historical document analysis, the study draws on primary sources such as census data, legislative records, and missionary archives. Through thematic analysis, the article identifies distinct religious dissemination patterns, power asymmetries, and socio-political shifts. While Islam grew through local initiatives and figures like Tun Datu Mustapha, Christianity gained rapid ground through colonial endorsement. Comparative demographic trends from 1921 to 1960 reveal a disproportionate increase in Christian converts, reflecting structural imbalances. The study concludes that Sabah’s religious identity is the product of colonial-era negotiations between religious institutions, political structures, and indigenous agency— dynamics that continue to shape the region’s postcolonial religious landscape.